Specificity, conditions and trends in modern public financial management in Poland - Ostachowski, Paweł; Sanetra-Półgrabi, Sabina (Scientific Journal of Bielsko-Biala School of Finance and Law, 2022)
The article deals with the issues of contemporary conditions and trends in public finance management in Poland. Starting from the classic concept of Peter Drucker that management is therefore not a set of individual and isolated activities, but the process of performing certain things with other people, work tries to justify in the first place that public finance is a special area of management, and then present the specific features of this space, which means that the direct implementation of commercial management techniques in it is neither easy nor fully possible. The main hypothesis of the work is the assumption that the processes and management innovations appearing in the commercial sector inevitably cause a slow transformation of management, also in the public sector, towards the optimization of its management processes and cost optimization, as well as the acquisition and use of human resources. The article also emphasizes that public finance in Poland is still a sector characterized by organizational distinctness and expenditure discipline, which limit the full transposition of commercial management models. It also presents the current trends in the management of this sector in a summary, pointing to talent management as one of the possible further ways to improve the functioning of this sector. The way to test the hypotheses of the work in this case are various research methods, both the analysis of the literature on the subject and the analysis of legislation giving an image of the possibilities and limitations of the implementation of managerial management in administration and public finances in Poland.